Bachelor degree participation in vocational institutions: examining the determinants of participation. (3rd May 2020) - Koshy, Paul; Webb, Sue; Dockery, Alfred M.; Knight, Elizabeth
ABSTRACT: Recent studies in Australia have found that bachelor's degree participation in vocational institutions in Australia tends to skew towards students from high and middle socioeconomic status (SES) backgrounds. This outcome runs counter to overall vocational participation which is dominated by students from low and middle SES backgrounds. This paper uses data from the Longitudinal Surveys of Australian Youth (LSAY) to confirm findings from a mixed-methods study on bachelor courses in vocational institutions by school leaver-aged students. It characterises the student population in such courses and examines evidence on the influence of determinants of bachelor participation in vocational institutions, in relation to measures of family background, wealth and cultural status and school type. It is found that students entering bachelor programs in vocational education have higher household levels of cultural possession, are more likely to plan to enter university, and have higher self-assessments of academic ability than those undertaking traditional vocational qualification pathways, but lower than those who undertook bachelor qualifications at university.